Pengaruh Penggunaan Tepung Daun dan Batang Ubi Jalar (Ipomoea Batatas L) Dalam Ransum Terhadap Performans dan IOFC Ternak Babi Peranakan Landrace Fase Grower - Deor, Liberatus Frangkolino; Dodu, Tagu; Marlene Nalley, W. (Journal of Comprehensive Science, 2024)
Pig farming has great potential to be developed because it is efficient in converting feed into meat. Feed is the largest cost component in production, which is about 60-80% of the total cost. Landrace pigs are the main choice of breeders because of their fast growth and docile temperament. However, the high price of factory-made feed encourages farmers to look for alternative feed ingredients, including agricultural waste such as sweet potato leaves (Ipomea batatas L), which are rich in nutrients and relatively cheap (Sihombing, 2016). Sweet potato leaves contain 25.51% crude protein and various other important nutrients, but they also contain anti-nutrient substances such as tannins. The aim of this research was to determine the effect of giving of leaf and stems sweet potato meal (SPM) on performa and income over feed costs (IOFC) in the grower pig. A total of 12 female landrace pigs aged 3-4 months with an average body weight of 55.5 kg (CV = 24.23%) were used in this study. The experimental method used a randomized block design, with 4 treatments and 3 replications. The treatments tried consisted of R0: ration without sweet potato leaf and stems meal sweet potato (SPM), R1: ration 5% (SPM), R2: ration 10% (SPM) meal, R3: ration 15% (SPM). The variables studied were performa and Income Over Feed Cost (IOFC).The variables measured are ration consumption, body weight gain, ration conversion and Income Over Feed Cost (IOFC). The results of the analysis of variance (ANOVA) showed that the treatment had no significant effect (P>0.05) on feed consumption, body weight gain, feed conversion and Income Over Feed Cost of research pigs. It can be concluded that the use of leaf and stems meal sweet potato 5%, 15% in pig rations provide the same response to provide the same effect on body weight gain, ration conversion and Income Over Feed Cost (IOFC). leaves and stems sweet potato can be used up to 15%.